You're Sad, Then I'll "Like" Computer-mediated communication (CMC) perspective - Rulli Nasrullah; Kiky Ridzky; Musyaffa Musyaffa (Jurnal Ilmiah Syi'ar, 2025)
Computer mediated communication or CMC is essentially represented by the text. Text in the interaction is not only displays the message to be delivered, but also embodied the meaning of the expression as well as expression in the face to face communication. However, the presence of Facebook as social networking sites and iconic "Like" or Like Button in the comment section to give a new direction of the emotional meaning of the interactions that occur. Do not like emoticons representing expressly or at least close to the other person's emotions, iconic "Like" on Facebook is not explicitly represent the meaning of  "Likes" of the status or situation revealed by the entity. Iconic "Like" transformed into a free text meaning which requires an entity on the internet make sense of these icons are free as well.